Clinical performance of metagenomic next-generation sequencing for the rapid diagnosis of talaromycosis in HIV-infected patients - Mao, Yuhuan; Shen, Hui; Yang, Caili; Jia, Qunying; Li, Jianying; Chen, Yong; Hu, Jinwei; Huang, Weiliang (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Background: Talaromycosis is an invasive endemic mycosis caused by the dimorphic fungus Talaromyces marneffei (T. marneffei, TM). It mainly affects immunodeficient patients, especially HIV-infected individuals, which causes significant morbidity and mortality. Culture-based diagnosis takes a long turnaround time with low sensitivity, leading to treatment delay. In this study, we aimed to evaluate the performance of Metagenomic Next-Generation Sequencing (mNGS) for the rapid diagnosis of talaromycosis in HIV-infected patients. Methods: Retrospectively analysis was conducted in HIV-infected cases at Changsha First Hospital (China) from January 2021 to March 2022. Patients who underwent routine microbiological examination and mNGS testing in parallel were enrolled. The clinical final diagnosis was used as a reference standard, and cases were classified into the TM group (60 cases) and the non-TM group (148 cases). The clinical performances of mNGS were compared with culture and serum Galactomannan (GM). The mixed infections detected by mNGS were analyzed. The impact of mNGS detection on treatment was also investigated. Results: The sensitivity of mNGS test reached 98.3% (95% CI, 89.7-99.9), which was significantly higher than culture (66.7% [95% CI, 53.2-77.9], P < 0.001) and serum GM (83.3% [95% CI, 71.0-91.2], P < 0.05). The specificity of 98.6% (95% CI, 94.7-99.7) was similar to culture (100.0% [95% CI, 96.8-100.0], P = 0.156), and superior to serum GM (91.9% [95% CI, 85.9-95.5], P < 0.05). In bronchoalveolar lavage fluid (BALF) samples, the positive rate of mNGS was 97.6%, which was significantly higher than culture (28.6%, P <0.001). mNGS has excellent performance in the identification of mixed infection in TM group patients. Cytomegalovirus, Epstein-Barr virus and Pneumocystis jirovecii were the most common concurrent pathogens. In summary, 60.0% (36/60) patients were added or adjusted to antimicrobial therapy after mNGS test. Conclusion: mNGS is a powerful technique with high specificity and sensitivity for the rapid diagnosis of talaromycosis. mNGS of BALF samples may be a good option for early identification of T. marneffei in HIV-infected individuals with manifestations of infection. Moreover, mNGS shows excellent performance in mixed infection, which benefits timely treatment and potential mortality reduction.